OPTIMALISASI PEMANFAATAN PELEPAH KELAPA SAWIT SEBAGAI SUMBER BAHAN ORGANIK TANAH DIPERKEBUNAN KELAPA SAWIT DENGAN PERLAKUAN AMANDEMEN DAN BIODEKOMPOSER - Mardiana Wahyuni; W A Tambunan; Marshal Arifin Sinaga (Institut Teknologi Sawit Indonesia, 2017)
Soil organic matter is hoarding from the remains ofplants and animals that most have experienced weathering and reshaping. Such organic materials are in Active weathering and attack prey remains of micro. Organic matter has an important role in determining the ability ofthe soil to supportplant, so that ifthe levels ofsoil organic matter decline soil capability, support crop productivity also decreased. At the plant has not been producingpalm oil sourcing organic ingredients is Mucuna bracteata and on oilpalm plants produce organic material is the source ofthe empty Palm bunches (TKKS) and the stem o fpalm oil. Based on this research required influence the decomposition stem o fpalm oil with preferential treatment and microorganisms against Amendment Magnesium soil. The research was carried out in theAfdelingl Field Limau Mungkur PT. Perkebunan Nusantara II.Research on time for six months, from January - June 2016. This research uses complete block design with 5 treatments and 3 replicates. Testing parameters are arranged on a list offingerprints and do Real differentfrom the smallest test (BNT) and level 5% and 1%. The results showed that changes the color of the stem may be fastest on the treatment with the addition ofP2 CaC03 (Limestone), changes the texture o fthe stem that is experiencing thefastest decomposition i.e. on treatment ofP2 (CaC03), decreased levels of C/N could befastest at the treatment the P2 (CaC03) with the c/n early stem is 149.86 be 97.88 at 3 months after application (BSA) and became 46.53 at 5 months After application (BSA) , and the levels o f Mg soil did not differ markedly because no significant changes towards the levels ofMg soil.